2021
DOI: 10.3389/fnano.2021.710612
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Formation of Nanoparticles Prepared by Magnetron Sputtering Onto Liquids: Gold Sputtered Onto Castor Oil as a Case Study

Abstract: Magnetron sputter deposition of metal targets over liquids allows producing colloidal solutions of small metal nanoparticles (NPs) without any additional reducing or stabilizing reagents. Despite that this synthetic approach is known for almost 15 years, the detailed mechanism of NP formation is still unclear. Detailed investigations must be carried out to better understand the growth mechanism and, ultimately, control the properties of the NPs. Here, the combination of the gold (Au) target and castor oil, a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…An increase in temperature leads to a decrease in viscosity and hence to a higher number of collisions yielding larger NPs. Thus, depositions with a HiPIMS power supply [131,132] might be used as an alternative to the annealing process [174][175][176] for producing larger metallic NPs.…”
Section: Type Of Sputtering Plasmamentioning
confidence: 99%
See 4 more Smart Citations
“…An increase in temperature leads to a decrease in viscosity and hence to a higher number of collisions yielding larger NPs. Thus, depositions with a HiPIMS power supply [131,132] might be used as an alternative to the annealing process [174][175][176] for producing larger metallic NPs.…”
Section: Type Of Sputtering Plasmamentioning
confidence: 99%
“…Yonezawa’s group [ 120 ] showed that only the absorbance of the Au NP solutions increases proportionally with the current (from 10 to 30 mA) but not the size of the NPs after sputtering onto PEG. It was also shown that the size of metal NPs does not depend on the sputter power in the case of sputtering iron (Fe) onto the surface of silicon oil [ 130 ] and in the case of sputtering of Ag or Au onto castor oil [ 131 132 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations